2019
DOI: 10.3171/2017.9.jns17545
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery for trigeminal neuralgia: a systematic review

Abstract: OBJECTIVES The aims of this systematic review are to provide an objective summary of the published literature specific to the treatment of classical trigeminal neuralgia with stereotactic radiosurgery (RS) and to develop consensus guideline recommendations for the use of RS, as endorsed by the International Society of Stereotactic Radiosurgery (ISRS). METHODS The authors performed a systematic review of the English-language literature from 1951 up to December 2015 using the Embase, PubMed, and MEDLINE database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
133
3
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(153 citation statements)
references
References 147 publications
(240 reference statements)
8
133
3
9
Order By: Relevance
“…Furthermore, re-irradiation and presence of MS were independent predictors of the occurrence of numbness. The results of this series in terms of pain relief are consistent with those previously reported and suggest that image-guided robotic radiosurgery represents an effective treatment of TN [7,8,10,17]. Our results are indeed slightly superior to those previously published by Romanelli et al (n = 138 pts.…”
Section: Key Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, re-irradiation and presence of MS were independent predictors of the occurrence of numbness. The results of this series in terms of pain relief are consistent with those previously reported and suggest that image-guided robotic radiosurgery represents an effective treatment of TN [7,8,10,17]. Our results are indeed slightly superior to those previously published by Romanelli et al (n = 138 pts.…”
Section: Key Resultssupporting
confidence: 92%
“…Alternative techniques aim to modulate the trigeminal nociceptive pathways either by percutaneous lesioning of the Gasserian ganglion or by irradiation of the cisternal portion of the nerve using stereotactic radiosurgery (SRS) [1,6,7]. Clinical experience regarding TN treatment using SRS is based mainly on single isocenter Gamma knife radiosurgery (GKS) treatments [8]. Typically GKS results in up to 92% pain relief within 12 months; however, the pain relapse rate during follow-up is remarkable [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The preferred target for GKRS has evolved from the trigeminal ganglion itself to the retrogasserian region and to the root entry zone. A meta-analysis of GKRS outcomes reported that pain relief ranged from 69 to 85% at one year, falling to 38 to 52% at 5 years and 30 to 45.3% at 10 years [ 56 , 68 ]. Onset of pain relief is delayed, ranging from 15 to 78 days on average, up to 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the technique has been refined and great care is taken to target the precise area to be treated to optimize pain control and minimize complications. 16 It has been reported that a lesion close to the root exit zone of the TN is very effective on pain, although this type of lesion carries the possibility of unpleasant collateral symptoms (hypoesthesia). Therefore, when feasible and depending on intracisternal TN length, the isocenter should be located distally from the brainstem 16 ; doses generally used for these treatments range between 80 and 90 Gy (maximal dose).…”
Section: Discussionmentioning
confidence: 99%